Efficacy of Pneumatophorus japonicus meat as an iron fortificant in whole‐wheat flour in preventing iron deficiency. Issue 1 (12th December 2022) - Tan, Beibei; Sun, Bolun; Yang, Changjie; Li, Chao; Zhang, Jinjie; Yang, Wenge
Abstract : Abstract: Iron deficiency anemia (IDA) is a global health concern affecting one‐third of the world's population, particularly those dominated by plant‐based food. Fortifying staple foods with iron has been an effective strategy for preventing IDA. Pneumatophorus japonicus is an essential economic fish in China. Pneumatophorus japonicus dark meat is usually underutilized as a byproduct, though it contains bounteous nutrients, including heme iron (10.50 mg/100 g). This study aimed to investigate the iron bioavailability of P. japonicus dark meat and to evaluate its potential as an iron fortifier for whole‐wheat flour, a typical staple food, using an in vitro digestion/Caco‐2 cell culture system. Our results suggested the excellent iron bioavailability of P. japonicus dark meat in comparison with beef (a heme dietary iron reference), whole‐wheat flour (a non‐heme dietary iron reference), and FeSO4 (a conventional iron supplement). The addition of P. japonicus dark meat notably enhanced iron solubility, bioavailability, and protein digestibility of whole‐wheat flour. The flour‐dark meat mixture yielded 1.96 times the iron bioavailability compared to beef per gram. The iron bioavailability was further improved by adding vitamin C, a commonly used dietary factor, at the Vc/iron mass ratio of 2:100‐5:100. Our findings reveal the promise of P. japonicus dark meat as a significant source of bioavailable iron, providing a basis for developing fish byproducts as alternatives for iron supplementation. Practical Application: This study investigated the iron bioavailability of Pneumatophorus japonicus meat using in vitro digestion/Caco‐2 cell culture system. These results could be used to improve the utilization of Pneumatophorus japonicus byproduct (dark meat) and develop the potential of the byproduct as an iron fortifier for whole‐wheat flour.